Functional Roles of D2-Lys317 and the Interacting Chloride Ion in the Water Oxidation Reaction of Photosystem II As Revealed by Fourier Transform Infrared Analysis - Suzuki,H; Yu,J; Kobayashi,T; Nakanishi,H; Nixon,PJ; Noguchi,T (BIOCHEMISTRY, 2013)
Photosynthetic water oxidation in plants andcyanobacteria is catalyzed by a Mn4CaO5 cluster within thephotosystem II (PSII) protein complex. Two Cl− ions boundnear the Mn4CaO5 cluster act as indispensable cofactors, buttheir functional roles remain to be clarified. We haveinvestigated the role of the Cl− ion interacting with D2-K317 (designated Cl-1) by Fourier transform infraredspectroscopy (FTIR) analysis of the D2-K317R mutant ofSynechocystis sp. PCC 6803 in combination with Cl−/NO3−replacement. The D2-K317R mutation perturbed the bands inthe regions of the COO− stretching and backbone amidevibrations in the FTIR difference spectrum upon the S1 → S2 transition. In addition, this mutation altered the 15N isotope-editedNO3− bands in the spectrum of NO3−-treated PSII. These results provide the first experimental evidence that the Cl-1 site iscoupled with the Mn4CaO5 cluster and its interaction is affected by the S1 → S2 transition. It was also shown that a negative bandat 1748 cm−1 arising from COOH group(s) was altered to a positive intensity by the D2-K317R mutation as well as by NO3−treatment, suggesting that the Cl-1 site affects the pKa of COOH/COO− group(s) near the Mn4CaO5 cluster in a commonhydrogen bond network. Together with the observation that the efficiency of the S3 → S0 transition significantly decreased in thecore complexes of D2-K317R upon moderate dehydration, it is suggested that D2-K317 and Cl-1 are involved in a protontransfer pathway from the Mn4CaO5 cluster to the lumen, which functions in the S3 → S0 transition.